Exposure of humpback whales to unregulated whalewatching activities in their main reproductive area in New Caledonia - Schaffar , Aline; Garrigue, Claire; Constantine , Rochelle (J. Cetacean Res. Manage., 2023)
Whale- and dolphin-watching activities are demonstrating a strong growth worldwide, raising concern of their potential impacts on cetacean populations and emphasising the need for management. Humpback whales recently have become the focus of an important tourism industry in the South Pacific, particularly in New Caledonia, where operators focus on a small population of humpback whales on their main breeding ground. Despite considerable growth since it began in 1995, the industry remains unregulated. Between 2005 and 2007, a study was conducted to assess the impact of whalewatching activities on the behaviour of humpback whales in New Caledonia. All data were collected from a land-based research station using a theodolite. Results show that 54% of all humpback whale groups sighted were exposed to whalewatching boats. Each group was watched simultaneously by an average of 2.5 boats. More than three boats were present within 300m of a group of whales 30% of the time. The length of time a group of whales was observed in the presence of boats each day was an average of one hour and 52 minutes but exceeded two hours 37% of the time. On average, each boat spent 52 minutes with the same group of whales. The closest point of approach was less than 100m for 86% of groups with a calf and 55% of non-calf groups. These results indicate that humpback whales are exposed to whalewatching boats in New Caledonia at a level exceeding the limits commonly recommended by management measures worldwide. Such exposure could be particularly problematic for mother-calf pairs, more vulnerable to threats. The strong site fidelity of individuals on this breeding ground raises concern of potential cumulative impacts. Management measures should be implemented to regulate whalewatching activities and ensure the conservation of this small, endangered population of humpback whales.